Komposisi Hasil Tangkapan Longline di Pelabuhan Benoa, Provinsi Bali - Wattimena, Adolf Krisna Mahendra; Dirgayusa, I Gusti Ngurah Putra; Puspitha, Ni Luh Putu Ria (CV. Ulil Albab Corp, 2025)
Tuna longline fishing was first introduced tothe Indonesian people around 1954, pioneered by theCenter for Marine Fisheries, and for the first time in1962, long line tuna fishing was attemptedcommercially by BPU Fisheries. Fisheries.Longlinetuna fisheries in Indonesia, especially in the IndianOcean, began to develop since the establishment of thestate company PT (Persero) Fisheries Samudra Besarin 1972 which is located in Benoa, Bali. Benoa Harboris the main port in Bali Province and is one of thebases for the distribution of tuna fish in Indonesiaapart from Muara Baru (Jakarta), Pelabuhan Ratu(West Java) and Cilacap (Central Java). As one of themain tuna fishing ports, Benoa Harbor is the base forindustrial scale tuna fishing vessels operating in thewaters of the Indian Ocean.